Imaging Diagnosis of Interstitial Pneumonia with Emphysema (Combined Pulmonary Fibrosis and Emphysema) - Fumikazu Sakai; Junya Tominaga; Akiko Kaga; Yutaka Usui; Minoru Kanazawa; Takashi Ogura; Noriyo Yanagawa; Tamiko Takemura (Pulmonary Medicine)
Based on clinical and radiological findings, Cottin defined combined pulmonary fibrosis and emphysema (CPFE) as pulmonary emphysema in the upper lungs and interstitial pneumonia in the lower lungs with various radiological patterns. Pathologic findings of CPFE probably corresponded with diffuse interstitial pneumonia with pulmonary emphysema, emphysema with fibrosis, and the combination of both. We described reported radiological findings of CPFE.